Farmers′ use of climate change adaptation strategies and their impacts on food security in Kenya - Girma Gezimu Gebre; Yuichiro Amekawa; Asmiro Abeje Fikadu; Dil Bahadur Rahut (Climate Risk Management, 2023)
Climate change threatens the sustainability of food production among farmers in Kenya who depend on rain‐fed agriculture. To minimize the negative impacts of climate change, farmers have sought to adopt different adaptation strategies. This study investigates factors influencing farmers’ choice of climate change adaptation strategies and associated effects on their food security in Kenya using data collected from 540 farmers from six counties. A multivariate probit, censored least absolute deviation (CLAD), and propensity score matching (PSM) models were employed to identify the determinants in the farmers’ choice of climate change adaptation strategies, the number of adaptation strategies adopted, and the effect of climate change adaptation strategies on their food security, respectively. Results show that planting drought-tolerant crop varieties (55%), growing diversified crops (34%), growing early maturing crops (22%), and diversifying the sources of household income (18%) were the four major adaptation strategies used by the farmers in the study area. Younger farmers and those with higher education levels are more likely to use these climate change adaptation practices. The number of adaptation strategies used was positively associated with male farmers, education level, family size, land size, farm income, extension contact, training, and information access. The farmers who adopt one adaptation strategy have higher food security status (approximately 7–11%) than those who do not. If they adopt two adaptation strategies, their food security status increases by approximately 11–14%; if they adopt three adaptation strategies, their food security status increases by nearly 12–15%; and if they adopt four adaptation practices, their food security status increases by about 14–18%, compared to those who do not adopt any strategy. Thus, the farmers’ climate change adaptation practices have positive food security effects in Kenya according to the number of adaptation strategies adopted.